A Review of Warm Mix Asphalt Technology: Technical, Eco-nomical and Enviromental Aspects (2015)
In general terms, warm mix asphalt (WMA) technology presents a wide potential for successful use in road works construction projects. However, concerns remain regarding the durability and behavior of WMA mixtures in the long term, which need to be addressed. This review focuses on the technical, economic and environmental advantages and disadvantages. The review concludes that the main advantage, at the moment, of this technology concerns the environment. At the end of this work, the authors include certain recommendations for future works to continue strengthening the development of WMA technology.